Mandarin Chinese and English transfer during German language acquisition examples of structural properties transfer - Tan, Wan Ting; Ogasa, Nicole (Center for Enhancing Knowledge (CEK), United Kingdom, 2015)
The transfer between background languages and a target language is an important issue in foreign language acquisition. This study investigates the common German grammatical errors in written form, both morphological and syntactical, made by Malaysian Chinese students at Universiti Putra Malaysia (UPM), and the correlation of these errors with structural differences between the students’ background languages and the target language, i.e. the German language. The principal objective of this study is to ascertain the direct correlation between the influence of the students’ dominant language (Mandarin Chinese) and the language of instruction (English) with the extent of grammatical errors made whilst acquiring the German language. The students’ perception of typological similarity between background languages and the target language was investigated, as all participants predicted that German and English languages have typological similarity. The study results revealed that common errors were influenced by background language as well as intralingual transfer.